A comprehensive review of drying meat products and the associated effects and changes - Mediani, Ahmed; Hamezah, Hamizah Shahirah; Jam, Faidruz Azura; Mahadi, Nursyah Fitri; Chan, Sharon Xi Ying; Rohani, Emelda Rosseleena; Che Lah, Noor Hanini; Azlan, Ummi Kalthum; Khairul Annuar, Nur Aisyah; Azman, Nur Aida Fatin; Bunawan, Hamidun; Sarian, Murni Nazira; et al. (Frontiers in Nutrition, 2022)
Preserving fresh food, such as meat, is significant in the effort of combating global food scarcity. Meat drying is a common way of preserving meat with a rich history in many cultures around the globe. In modern days, dried meat has become a well enjoyed food product in the market because of its long shelf-life, taste and health benefits. It is well known that reducing the water content in meat helps in preventing microbial growth, which in turn prevents the presence of harmful substances in meat. However, drying the meat can change the characteristics of the meat itself, making consumers concerned on whether dried meat is safe to be consumed on a regular basis. It is important to consider the role of microbial enzymes and microbes in the preservation of their flavour when discussing dried meats and dried meat products. From 1990 until 2022, this review compiled important information from all available library databases and Internet searches on how the types of meat, ingredients and the used drying technologies influence the characteristics of dried meat in physicochemical, microbial, biochemical and safety features along with technological future prospects in the dried meat industry. The quality of dried meat can be influenced by a variety of factors, including its production conditions and the major biochemical changes that occur throughout the drying process, which are also discussed in this review. Additionally, the sensory attributes of dried meat are also reviewed, whereby the texture of meat and the preference of the market is emphasised. There are other aspects and concerning issues that are not covered in the research and we suggested them for future studies.